IMPLEMENTASI PERATURAN DAERAH KABUPATEN TANAH DATAR NO 5 TAHUN 2015 TENTANG IZIN USAHA JASA WARUNG INTERNET - Ikhsan Rahmat Hidayat; Feberi Yuliani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Tanah Datar is one area that is located in Indonesia, specifically in the province of West Sumatra, in the Tanah Datar stood internet cafes, internet cafes in Tanah Datar set in the Regional Regulation, which in regional regulation governs all concerned denganwarung internet, both owners of internet cafes, as well as users of internet cafes, but it is unfortunate, internet cafes located in Tanah Datar many will not fit with prescribed rules, many stalls internet-breaking rules such as internet cafes do not have a business license, warunjg internet which is open late at night, wear bulkhead exceed 40 cm, and let the children play school internet cafe wearing a school uniform. This study aims to determine how the implementation of Tanah Datar District Regulation No. 5 2015 On Public Internet service permit and the factors that affect the implementation of Tanah Datar District Regulation No. 5 2015 On Public Internet service permit.The theory used is the theory of Van meter and Horn in Sujianto that there are six variables determine the successful implementation of policies, among others, Standards and Objectives, Resources policies, Activity Observation and Communication interorganizational, Character Executive, Economic Conditions Social and Political Disposition or attitude Executor, Licensing Services Office of Tanah Datar, and who serves as key informant was the head of the field of Communications and Information Technology, Section Head of Investigation , and the head of Licensing. Data collection techniques such as interviews, observation and documentation. And data analysis using triangulation techniques.From the results of this research note that the implementation of Tanah Datar l, from the Department of spaciousness Perhub.kominfo less oversight, and lack of regulation of Internet cafés to socialize either directly or indirectly, from municipal police are still limitations Employees and Human Resources Shortage of qualified, and from the Office of Integrated Services Licensing is still at least owners of internet cafes that make business license because the number of internet cafés's Terms to create a business license internet cafes. Factors affecting the implementation of the Regional Regulation Tanah Datar, lack of communication carried out by implementing policies to the public, and lack of public awareness and the owner whitewater internet and many owners of internet cafes that do not approve of Tanah Datar District Regulation No. 5 of 2015 On Public Internet service permitKeywords: Licensing, Implementation, inhibiting factor